Assessment of depression, anxiety and stress among first year MBBS students of a public medical college, Bangladesh (Bangladesh Journal of Psychiatry, 2017)
Medical students confront significant academic, psychosocial and existential stressors for coping with new college and schedule,. So assessment of the symptoms of depression, anxiety and stress among medical students are essential to take necessary steps to treat or prevent any psychiatric morbidity. The objective of the study was to assess depression, anxiety and stress among the first year MBBS students. This was a cross sectional and descriptive study conducted in Khulna Medical College, Bangladesh from December 2009 to July 2010. For this purpose, 105 students fulfilling inclusion and exclusion criteria were taken as sample. They filled up personal data and the short-form Bangla version of DASS (DASS-21 BV) scale. The results showed that, the mean age of students was 18.8 years with male predominance (54.3%). Symptoms of depression, anxiety and stress were found among 54.3%, 64.8% and 59.0% of students respectively. Eighty five (81%) students either had depression, anxiety or stress alone or in combination. Combination of depression, anxiety and stress was highest (36.2%). No significant association was found between gender difference and depression, anxiety or stress. Age was positively correlated with depression (p=0.004) and stress (p=0.001). Percentage of 1st year MBBS students suffering from depression, anxiety and stress were very high. Adequate psychiatric services should be provided to manage these symptoms among medical students.Bang J Psychiatry June 2015; 29(1): 23-29